(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
Clusters are geographical concentrations of related companies, institutions and organisations that cooperate and compete in a specific sector to stimulate innovation, productivity and economic growth. Clusters in culture are important because they increase creativity and innovation among related companies, reduce costs and increase productivity, which strengthens regional economies and attracts investment. They also play a key role in preserving cultural heritage and identity, promoting local traditions and cultural heritage in a globalised world. In addition, clusters enable better cooperation and exchange of knowledge between different cultural actors, which leads to the development of new cultural and tourist offers. The article analyses the importance of clusters in the development of creative and cultural industries. Creative clusters are specific because of their instability and tendency to change, which affects their reputation and brands. The main advantage of these clusters is the preference for quality over quantity, which leads to greater innovation and success. Through the integration of companies, clusters increase specialisation, reduce costs and increase productivity, which strengthens regions and attracts investment. Also, clusters play a key role in preserving cultural treasures and identities, promoting local traditions and cultural heritage in a globalised world.